Perkembangan Kota Jombang masa kepemimpinan R.A.A. Soeroadiningrat 1910-1930 - Ananta Dharma Kusuma (Universitas Negeri Malang, 2022)
During the Dutch colonial administration, administratively Jombang was part of the Mojokerto Afdeling and only in 1910 underwent a separation into its own afdeling with the first regent R.A.A. Soeroadiningrat. Jombang Regency was then able to regulate its own government thanks to the decentralization law that was formed by the colonial parties in the early 20th century. This paper focuses on the problem of the dynamics of the development of Jombang City from being previously part of the Mojokerto afdeling to getting the authority to regulate its own government, at a glance about the biography of the first Regent of Jombang, namely RAA Soeroadiningrat and the last one discussing the development of infrastructure in Jombang City during the RAA Soeroadiningrat period. This paper uses a historical method consisting of topic selection, heuristics, interpretation and historiography. The purpose of this paper is to provide information to the public about the history of Jombang City during the colonial period, especially in the period 1910-1930. During the Dutch colonial administration, administratively Jombang was part of the Mojokerto Afdeling and only in 1910 underwent a separation into its own afdeling with the first regent R.A.A. Soeroadiningrat. Jombang Regency was then able to regulate its own government thanks to the decentralization law that was formed by the colonial parties in the early 20th century. This paper focuses on the problem of the dynamics of the development of Jombang City from being previously part of the Mojokerto afdeling to getting the authority to regulate its own government, at a glance about the biography of the first Regent of Jombang, namely RAA Soeroadiningrat and the last one discussing the development of infrastructure in Jombang City during the RAA Soeroadiningrat period. This paper uses a historical method consisting of topic selection, heuristics, interpretation and historiography. The purpose of this paper is to provide information to the public about the history of Jombang City during the colonial period, especially in the period 1910-1930.